-3x-10=6x-2

Simple and best practice solution for -3x-10=6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-10=6x-2 equation:


Simplifying
-3x + -10 = 6x + -2

Reorder the terms:
-10 + -3x = 6x + -2

Reorder the terms:
-10 + -3x = -2 + 6x

Solving
-10 + -3x = -2 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-10 + -3x + -6x = -2 + 6x + -6x

Combine like terms: -3x + -6x = -9x
-10 + -9x = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
-10 + -9x = -2 + 0
-10 + -9x = -2

Add '10' to each side of the equation.
-10 + 10 + -9x = -2 + 10

Combine like terms: -10 + 10 = 0
0 + -9x = -2 + 10
-9x = -2 + 10

Combine like terms: -2 + 10 = 8
-9x = 8

Divide each side by '-9'.
x = -0.8888888889

Simplifying
x = -0.8888888889

See similar equations:

| 4x+3y=385 | | 0.8x+3.5=2.1-0.3x | | 0.4-2.5= | | 15*-4= | | 15*.4= | | 12.1*6= | | 7(x+4)=107 | | 4p+2=8p-1 | | 0=-16t^2+1600t-14400 | | 300=x(x+20) | | x(x-1)=600 | | 9(a+b)+4(3a+2b)=y | | 8u-4=6u+4 | | 3h+4j-9(3h-5j+7k)= | | 280=x(4x+9) | | 55+X^2+-16x=0 | | 3/4n+15=10+2/5n | | 3/4(n+25)=10+2/5n | | -3x-x+5=0 | | 0=-34x+4x^3 | | (x-3)/5=2 | | 16x^2(13x-7)+23=25y-10x^2(33x+1) | | 45*78= | | 3y-9-(4-y)=2y-2 | | 2y^2+7y-30=0 | | 5s^3+4s^2-10s-8=0 | | 0.2x+0.6=-1.2 | | 3(x+5)+2(4x-5)=32 | | 4(4x-2.4)=2x-9.6 | | 2x+37=23 | | 6.6-9h=7.5 | | x-2*x-9=-10 |

Equations solver categories